Pengembangan produk sosis bernilai tambah dari thryssa mystax pada industri rumah tangga di Surabaya - Raharja, Kristian Triatmaja; Ferdina, Cucun Setya; Putri, Nindi Pramesthi Vardila; Fauziah, Nuraini; Pujiyani, Honesty; Fitro, Achmad (Poltekkes Kemenkes Aceh, 2025)
Background: The abundant Thryssa mystax resources in the Madura Strait hold strategic potential to support the local economy and food security. However, the traditional processing methods employed by IRT Jiddah and Barokah limit the enhancement of value-added and product competitiveness. This underscores the need for processing innovations, such as the development of fish sausage products, to improve quality, diversify products, and expand market opportunities. Objective: This study aimed to develop the most acceptable fish sausage formulation through hedonic sensory evaluation, while also analyzing the nutritional and microbiological characteristics of the selected product.Method: A completely randomized design was used with three treatments incorporating different proportions of Thryssa mystax (X1:250 g, X2:500 g, and X3:750 g). These were organoleptically evaluated by 40 semi-trained panelists to determine the best samples. The selected product was further analyzed for its nutritional composition and microbiological quality. Data were analyzed using one-way ANOVA at a 95% confidence level. This study was conducted in Surabaya from June to November 2024.Results: The organoleptic test results showed that the addition of Thryssa mystax had a significant effect on aroma, texture, and overall acceptance (p = 0,000), but not on color (p = 0,365) and taste (p = 0,503). X2 formulation (500 g) obtained the highest overall acceptance score of 4,3. These findings indicate that the X2 formulation not only provides sensory characteristics preferred by consumers but also has the potential to increase protein content and ensure stable sensory quality, making it suitable for application in small-scale household industry.Conclusion: Based on sensory evaluation across all attributes, the best formulation was X2. The X2 product contained 10,4% protein, 0,15% fat, 14,4% carbohydrates, 69,36% moisture, and 2,27% ash. Microbiological analysis showed a total plate count of 1,3 × 10⁵ CFU/g, which exceeded the maximum limit set by SNI.